Intellegence Vehicle Counting Menggunakan Metode Combination Value Saturation Pada Video Lalu Lintas - Guruh Adi Purnomo; Imam Cholissodin; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Transportation needs have become almost the needs of every activity undertaken by humans, and it greatly affects the number of vehicle growth in Indonesia according to data Traffic Corps of the State Police of the Republic of Indonesia noted, the number of vehicles that operate increases every year, causing congestion and the need for a solution to Overcome it. One solution to overcome the congestion by diverting the flow of vehicles to other lanes, and to overcome this is required to calculate the vehicle so that no congestion occurs again. Because at this time the calculation of the car is still done manually, then required a system that can calculate the vehicle automatically as